Penggunaan Model Discovery Learning dengan Metode Demostrasi Untuk Meningkatkan Ketuntasan Belajar Siswa SMAN 3 Bangkalan - Sartunut Sartunut (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2022)
This study aims to determine the mastery and student learning activities in learning activities through discovery learning models with demonstration methods on the material factors that affect the rate of reaction. The subjects of this study were students of class XI–MIPA-1 SMAN 3 Bangkalan. This research design uses classroom action research with two cycles and each cycle is carried out in two meetings. Each cycle consists of planned activities and observations, reflections and revised plans. The research was conducted in the odd semester of the 2018/2019 academic year. Methods of collecting data using tests, teacher and student activity observation sheets. From the results of these studies, it can be concluded that the application of the learning model of discovery learning with the demonstration method can increase the activity and learning mastery of class XI-MIPA-1 SMAN 3 Bangkalan on the Reaction Rate material. The percentage of classical completeness in the first cycle was 55.9% and in the second cycle increased to 82.4%. While the percentage of student activity was 70.7% in cycle 1 and cycle II increased to 80%.